Upaya Pemenuhan Hak Politik Pemilih Pemula Warga Penyandang Disabilitas Dalam Pemilihan Umum Tahun 2019 Di Kecamatan Limboto Kabupaten Gorontalo (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
This research aims to find out and analyze efforts to fulfill political rights for first-time voters with disabilities in the general election in Gorontalo Regency in 2019 and to find out and analyze the factors inhibiting the fulfillment of political rights for first-time voters with disabilities in the general election in Gorontalo Regency in 2019 , based on the title raised in this research, researchers see the weakness of Indonesia's defenses from attacks by things that endanger society, thousands of illegal drugs have been circulating throughout Indonesia. This research uses empirical methods. The data collection process examined by researchers in this research is primary data and secondary data. Data collection techniques that support and are related to this research are interviews, observation and literature study. The results of this research show that the KPU and the Government have ensured the implementation of efforts to respect and promote , protection and fulfillment of the rights of novice voters with disabilities to develop themselves and utilize all abilities according to their talents and interests to enjoy, participate and contribute optimally, safely, freely and with dignity in all aspects of national, state and social life. By socializing and expanding the network of first-time voters with disabilities to play an effective role in the general election system at all stages or parts of its implementation. Increasing the participation of people with disabilities in elections is also not easy. Every citizen has the right to social security necessary for a decent life and for full personal development. Every person with disabilities, elderly people, pregnant women and children have the right to receive special facilities and treatment. Accessibility problems are one of the factors that cause first-time voters with disabilities to not cast their votes optimally, as happened in Gorontalo where the Gorontalo Regency General Election Commission continuously coordinates with first-time voters with disabilities to ensure that these first-time voters with disabilities are still able to vote. exercise their rights when voting.